PENGARUH LAYANAN BIMBINGAN KELOMPOK TERHADAP PENURUNAN TINGKAT STRES SISWA KELAS VIII SMP IT AL-IKHSAN BOARDING SCHOOL RIAU - Umari, Tri Umari; Arlizon, Raja Arlizon (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study aims to determine the effect of group counseling services to decrease stress levels class VIII IT Smp Al-Ikhsan Boarding School Riau. The research method used was experimental method. To collect the data used purposive sampling technique. This research subject is class VIII SMP IT Al-Ikhsan Boarding School Lists academic year 2014/2015 amounted to 30 students. Results showed that group counseling can reduce stress levels of students, is seen from the results of the analysis tcount greater than the value ttable with significance level of 5% (7.8> 2:00). Thus Ho is rejected and Ha accepted, which means there is significantly different to the decline in stress levels of students before the post given group counseling services. Keywords: Guidance Services Group, stress